Atherosclerotic cardiovascular disease risk assessment in familial hypercholesterolemia: does one size fit all?. Issue 6 (December 2018) - Mata, Pedro; Alonso, Rodrigo; Pérez de Isla, Leopoldo
Abstract : Purpose of review: Familial hypercholesterolemia is a frequent genetic disease associated with lifelong elevation of LDL-cholesterol and premature atherosclerotic cardiovascular disease (ASCVD). Statins are the cornerstone of treatment. However, with the introduction of novel LDL-cholesterol-lowering therapies, it is necessary to identify familial hypercholesterolemia patients presenting a significantly high residual ASCVD risk. The aim of this review is to provide an update on the recent literature concerning cardiovascular risk stratification including the role of coronary imaging. Recent findings: Several factors have shown to be independent predictors of ASCVD in familial hypercholesterolemia. These include clinical scores with cardiovascular risk factors, coronary imaging and novel protein biomarkers. However, the recent introduction of the SAFEHEART risk-equation (SAFEHEART-RE) could allow a more accurate ASCVD risk prediction in familial hypercholesterolemia. Summary: This article highlights the SAFEHEART-RE as a model to predict incident ASCVD in familial hypercholesterolemia. This equation is a simple and widely applicable tool for use in every clinical setting. Furthermore, coronary atherosclerosis assessed by coronary computed-tomographic angiography (coronary-CTA) is independently associated to the cardiovascular risk estimated according to the SAFEHEART-RE. This equation, as well as coronary-CTA and new biomarkers, could increase individual ASCVD risk stratification and could improve the efficiency and the use of new lipid-lowering therapies in familial hypercholesterolemia.